1989
DOI: 10.1073/pnas.86.20.7904
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP is a mitogen for 3T3, 3T6, and A431 cells and acts synergistically with other growth factors.

Abstract: Extracellular ATP in concentrations of 5-50 gLM displayed very little mitogenic activity by itself but it caused synergistic stimulation of [3H]thymidine incorporation in the presence of phorbol 12-tetradecanoate 13-acetate, epidermal growth factor, platelet-derived growth factor, insulin, adenosine, or 5'-(N-ethyl) These findings raise the possibility that exogenous ATP acts as a growth factor, and this was implied in two recent papers (23, 24), where ATP was compared to "more conventional mitogens." However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 44 publications
(37 reference statements)
1
107
0
Order By: Relevance
“…Moreover, extracellular ATP may be of importance in the growth regulation of mammalian cells. Stimulation of DNA synthesis has been reported for a variety of cultured cells including mouse fibroblasts, A431 epidermoid carcinoma cells and DDT,-MF-2 vas deferens cells (Huang et al, 1989), in aortic smooth muscle cells (Malam-Souley et al, 1993;Erlinge et al, 1993), endothelial cells (Van Daele et al, 1992) and mesangial cells (Schulze-Lohoff et al, 1992). It has been reported that activation of PKC and phospholipase A2 and subsequent production of prostaglandin E2 and cyclic AMP formation are obligatory early steps in a pathway resulting in ATPdependent mitogenesis Huang et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, extracellular ATP may be of importance in the growth regulation of mammalian cells. Stimulation of DNA synthesis has been reported for a variety of cultured cells including mouse fibroblasts, A431 epidermoid carcinoma cells and DDT,-MF-2 vas deferens cells (Huang et al, 1989), in aortic smooth muscle cells (Malam-Souley et al, 1993;Erlinge et al, 1993), endothelial cells (Van Daele et al, 1992) and mesangial cells (Schulze-Lohoff et al, 1992). It has been reported that activation of PKC and phospholipase A2 and subsequent production of prostaglandin E2 and cyclic AMP formation are obligatory early steps in a pathway resulting in ATPdependent mitogenesis Huang et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Early observations, from the late 1970s on, already indicated nucleotides to equivocally affect thymocytes/lymphocyte mitogenesis/blastogenesis [147,[155][156][157][158][159][160][161]. Barankiewicz et al suggested that extracellular ATP catabolism may serve as a means of communication between B and T cells in lymphoid organs, with B lymphocytes but not T lymphocytes being the producers of adenosine via ATP breakdown, and T lymphocytes being the recipients of this signal [162].…”
Section: B and T Cellsmentioning
confidence: 99%
“…At lower concentrations, however, mitogenic actions of extracellular ATP, mediated by P2-purinoceptors, have been reported in numerous cell types, including aortic smooth muscle cells (Wang et al, 1992), mesangial cells (SchulzeLohoff et al, 1992;Ishikawa et al, 1994) and the human ovarian cancer cell lines, OVCAR-3 (Popper and Batra, 1993) and SKOV-3 (Batra and Fadeel, 1994). ATP has also been shown to act as a co-mitogen in concert with other growth factors to enhance cellular proliferation in transformed mouse fibroblasts and epidermoid carcinoma A431 cells (Huang et al, 1989) and aortic smooth muscle (Wang et al, 1992).…”
mentioning
confidence: 99%